2016
DOI: 10.1016/j.cognition.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Description and experience: How experimental investors learn about booms and busts affects their financial risk taking

Abstract: A few years ago, the world experienced the most severe economic crisis since the Great Depression. According to the depression baby hypothesis, people who live through such macroeconomic shocks take less financial risk in their future lives (e.g., lower stock market participation). This hypothesis has previously been tested against survey data. Here, we tested it in a simulated experimental stock market (based on the Spanish stock index, IBEX-35), varying both the length of historical data available to partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 29 publications
5
35
0
Order By: Relevance
“…Learning from both the vicarious-learning intervention and from experience of the dollar auction did not have a stronger effect than first-hand learning (from experiencing the dollar auction) alone. This finding is in line with recent evidence from the effects of different types of experience on investment decisions: Lejarraga, Woike, and Hertwig (2016) showed that experience in investing in funds allows for a different kind of learning than analyzing the fund's past performance without investing.…”
Section: Discussion Experimentssupporting
confidence: 91%
“…Learning from both the vicarious-learning intervention and from experience of the dollar auction did not have a stronger effect than first-hand learning (from experiencing the dollar auction) alone. This finding is in line with recent evidence from the effects of different types of experience on investment decisions: Lejarraga, Woike, and Hertwig (2016) showed that experience in investing in funds allows for a different kind of learning than analyzing the fund's past performance without investing.…”
Section: Discussion Experimentssupporting
confidence: 91%
“…Second, users can gain experience with probabilistic information and their various representations before their understanding is tested or before they evaluate the representations (Hogarth and Soyer, ; Lejarraga et al . ; Wulff et al . , discuss the importance of experience in decision making).…”
Section: Three Diverse Practical Applicationsmentioning
confidence: 99%
“…This is in line with research showing that good performance in repeated tasks relies on executing special purpose visual routines that process only the minimum required information (Hayhoe, 2000), and that this allows for faster learning with fewer errors (Hullinger, Kruschke, & Todd, 2015). Consistent with existing work in behavioral finance (Chang, Solomon, & Westerfield, 2016;Kuhnen, Rudorf, & Weber, 2017), focusing on the price change history directly before making the choice could also indicate a lower cognitive dissonance or more accurate updating of one's beliefs, no longer distorted by information about one's subjective experience with the stock (also see Lejarraga, Woike, & Hertwig, 2016, for more work on learning from experience versus description in experimental stock markets).…”
Section: Properties Of the Machine Learning Algorithmmentioning
confidence: 63%